2001
DOI: 10.1046/j.1365-2761.2001.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of manual removal and ivermectin gavage for control of Salmincola californiensis (Wilson) infestation of chinook salmon, Oncorhynchus tshawytscha (Walbaum), captive broodstocks

Abstract: Captive broodstocks of spring chinook salmon, Oncorhynchus tshawytscha, were initiated from collections of naturally produced parr from the Lemhi River, a tributary of the Salmon River, ID, USA. These ®sh were subsequently demonstrated to be infested with the copepod parasite Salmincola californiensis. The initial prevalence of visible adult parasites for 4 years of observations made shortly after collection varied from 19.7 to 71.6%. Both the prevalence and intensity of the infestation increased in the freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Due to the success of Ivermectin in treating the parasitic freshwater Copepod Salmincola californiensis in this project's pilot studies conducted in 2000 , we diluted it with saline (1:30) and injected 1 to 3 mL into the Downloaded by [University of Prince Edward Island] at 23:56 06 February 2015 posterior end of the fish's esophagus, using a plastic syringe (Johnson and Heindel 2001). Fish were also given an initial injection of oxytetracycline and fed the dietary supplement hwwiegandt multi vit (Wiegandt GmbH -Aquaristics Products, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the success of Ivermectin in treating the parasitic freshwater Copepod Salmincola californiensis in this project's pilot studies conducted in 2000 , we diluted it with saline (1:30) and injected 1 to 3 mL into the Downloaded by [University of Prince Edward Island] at 23:56 06 February 2015 posterior end of the fish's esophagus, using a plastic syringe (Johnson and Heindel 2001). Fish were also given an initial injection of oxytetracycline and fed the dietary supplement hwwiegandt multi vit (Wiegandt GmbH -Aquaristics Products, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The avermectin emamectin benzoate (EB) (Slice ® ), which is the latest introduced treatment, has been in use from 1999. The main use of avermectins in aquaculture is against infestations with ectoparasitic copepods, among them Calanus rogercresseyi, on farmed sal mon in Chile (Bravo 2003), Salmincola californiensis in Chinook salmon (Johnson & Heindel 2001) and Lernathropus kroyeri in sea bass (Athanassopoulou et al 2001). However, bioassays (Westcott et al 2008) have demonstrated reduced sensitivity to EB in louse strains in various countries (Lees et al 2008a,b, Horsberg 2012, Igboeli et al 2012, Carmichael et al 2013, Espedal et al 2013, Ljungfeldt et al 2014, and a recent study demonstrated that genes influencing resistance to this chemical were rapidly spread among salmon lice on both sides of the Atlantic (Besnier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…primarily attach to the gills, opercula, and mouth cavity of fish (Kabata and Cousens 1973), often resulting in severe gill damage and respiratory stress (Sutherland and Wittrock 1985;Mitchum 1995;Duston and Cusack 2002;Roberts et al 2004). The control methods tested to date have had limited success (Johnson and Heindel 2001;Duston and Cusack 2002;Modin and Veek 2002;Roberts et al 2004;Lester and Hayward 2006), and no chemotherapeutic treatments have been approved for use in the United States. SLICE (0.2% emamectin benzoate [EB]) is an in-feed treatment developed by Intervet/Schering-Plough (now Merck) Animal Health (Roseland, New Jersey) to control infestations of ectoparasitic crustacean sea lice (e.g., Lepeophtheirus salmonis and Caligus elongatus) in seawater-reared Atlantic salmon Salmo salar (Stone et al 1999(Stone et al , 2000b(Stone et al , 2000cISPAH 2003).…”
mentioning
confidence: 99%